2011
DOI: 10.1308/003588411x13008842578536
|View full text |Cite
|
Sign up to set email alerts
|

A case of widespread aortic thrombosis secondary to acute severe pancreatitis

Abstract: A 29-year-old male was admitted with a 3-day history of increasing epigastric and back pain. With a raised serum amylase within the diagnostic limits for acute pancreatitis and with deranged liver function tests, the patient was started on the standard treatment for acute pancreatitis. This included intravenous fluids, oxygen, urine output monitoring with strict fluid balance charting, a proton-pump inhibitor, venous thromboembolism prophylaxis and antibiotics (in accordance with our local policy).An abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Las trombosis arteriales son la complicación vascular más infrecuente de la pancreatitis; un estudio prospectivo que buscó evaluar las complicaciones arteriales de 189 pacientes con pancreatitis aguda no encontró trombosis arteriales (10) y los reportes de estas complicaciones han sido limitados a series de casos. Durante la revisión de la literatura, se encontraron reportes de caso de trombosis de la arteria mesentérica superior (11,12) , arterias renales (13) , trombosis aórtica (14) y del tronco celíaco (15) . No se encontraron reportes de arteria hepática.…”
Section: Discussionunclassified
“…Las trombosis arteriales son la complicación vascular más infrecuente de la pancreatitis; un estudio prospectivo que buscó evaluar las complicaciones arteriales de 189 pacientes con pancreatitis aguda no encontró trombosis arteriales (10) y los reportes de estas complicaciones han sido limitados a series de casos. Durante la revisión de la literatura, se encontraron reportes de caso de trombosis de la arteria mesentérica superior (11,12) , arterias renales (13) , trombosis aórtica (14) y del tronco celíaco (15) . No se encontraron reportes de arteria hepática.…”
Section: Discussionunclassified
“…Experimental and clinical studies [15,16] have found that LMWH can lower the expression of tumour necrosis factor-α and interleukin-6; reduce the risk of microthrombus formation; relieve microcirculatory issues in the pancreas, kidney, lung, and brain; and lower the fatality rate in patients with severe acute pancreatitis by down-regulating the expression of serum endothelin-I and the activity of NF-κB. Mishreki et al [17] compared the curative effects and safety of LMWH and unfractionated heparin in the treatment of deep venous thrombosis and found that LMWH had a better curative effect and better safety.…”
Section: Discussionmentioning
confidence: 99%
“…Cases reported thrombus development in the abdominal aorta and its branches, such as the superior mesenteric artery and renal arteries. A case report showed widespread aortic thrombi with sparing of the celiac trunk, splenic artery, common hepatic artery, and superior mesenteric artery[ 24 ]. Arterial thrombosis in pancreatitis can be unpredictable, with a case presenting with intracardiac thrombus following pancreatitis.…”
Section: Arterial Thrombosismentioning
confidence: 99%